Functioning of transmembrane receptors in cell signaling - Bradshaw, Ralph A., 1941-; Dennis, Edward A. (Amsterdam ; Academic Press, 2011)
'Cell signaling, which is also often referred to as signal transduction or, in more specialized cases, transmembrane signaling, is the process by which cells communicate with their environment and respond temporally to external cues that they sense there. All cells have the capacity to achieve this to some degree, albeit with a wide variation in purpose, mechanism, and response. At the same time, there is a remarkable degree of similarity over quite a range of species, particularly in the eukaryotic kingdom, and comparative physiology has been a useful tool in the development of this field. The central importance of this general phenomenon (sensing of external stimuli by cells) has been appreciated for a long time, but it has truly become a dominant part of cell and molecular biology research in the past three decades, in part because a description of the dynamic responses of cells to external stimuli is, in essence, a description of the life process itself. This approach lies at the core of the developing fields of proteomics and metabolomics, and its importance to human and animal health is already plainly evident'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cell interaction; Membrane proteins; Cellular signal transduction; Cell Communication -- physiology; Membrane Proteins; Signal transduction